1991
DOI: 10.1002/apmc.1991.051840117
|View full text |Cite
|
Sign up to set email alerts
|

A DSC investigation on the stabilizer distribution in PVC blends

Abstract: The distribution of a liquid organotin stabilizer between the phases of heterogeneous poly(viny1 chloride) (PVC) blends has been studied by differential scanning calorimetry (DSC). This method can be used even at low stabilizer concentrations. At concentrations > 1 wt.4'0 the stabilizer can be detected in both phases of a PVCISAN (poly(viny1 chloride)/poly(styrene-co-acrylonitrile)) blend. At lower concentrations no stabilizer could be found in the SAN phase. Determination of the induction period of thermal de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1992
1992
2008
2008

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…However, a weight loss about 0.3%, observed under similar severe experimental heating conditions, implies the depletion of some ingredients, to a certain extent, acting as plasticizer. 28 The cooling section of the DSC curves indicates the same transition of about 80ЊC.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…However, a weight loss about 0.3%, observed under similar severe experimental heating conditions, implies the depletion of some ingredients, to a certain extent, acting as plasticizer. 28 The cooling section of the DSC curves indicates the same transition of about 80ЊC.…”
Section: Resultsmentioning
confidence: 97%
“…However, neither the samples after heat treatment at 180ЊC on heating region nor any of the samples on cooling region of DSC curves showed such a peak. Braun et al 28 observed that the glass transition temperature of PVC samples with heat stabilizers attained after consecutive annealing up to 200ЊC at a value of the PVC samples without stabilizer. They attributed this behavior to the consumption of stabilizer in the heating process.…”
Section: Resultsmentioning
confidence: 98%
“…The decrease in T g of the blends was not influenced only by AAC. It was proven that T g of PVC decreased in the presence of other miscible additives, such as thermal stabilizers 17. With regard to the neat polymer, AAC in the blends was no longer partially crystalline but was completely amorphous, and we supposed that intermixing of the polymers at a molecular level occurred.…”
Section: Resultsmentioning
confidence: 88%